Effect of Irrigation and Fertilizer Application on Growth of Teak (Tectona grandis) in Semi-arid Regions - Bheemaiah, G. (Indian Forester, 2004)
A field trial was carried out during 1995 , 1996 and 1997 at Students' Farm , College of Agriculture , Rajendranagar on sandy loam soils to find out the effect of irrigation and fertilizer on growth of Teak. DBH and height of Teak was found more with values of 0.111 m and 7.5 m (1997) where irrigation was given for every 10 days (I10). During other years also the I10 had beneficial effect on growth. Application of 300g urea/tree (N3) had resulted in more height (7.81m) , diameter growth (0.114m) and volume growth (0.052m3) during 1997 , where compared to other levels of urea. The interaction of irrigation and urea , did not affect the growth of Teak significantly. From the results it is apparent that the growth of Teak can be increased substantially with irrigation for every 10 days along with urea application on sandy loam soils of semi-arid tropical regions.